การวิเคราะห์การเปลี่ยนแปลงระยะยาวของผลสัมฤทธิ์ทางการเรียนสิ่งแวดล้อม : การเปรียบเทียบผลการวิเคราะห์ด้วยโมเดลเอชแอลเอ็ม และโมเดลลิสเรล - สุภารัตน์ เรือจันทึก (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purpose of this study was to compare the analysis results of change in environmental knowledge obtained from longitudinal analysis by HLM and LISREL models. The sample consists of 509 students in mathayomsuksa 2 in the academic year 1998. The research instruments were the test for environmental knowledge, the test of environmental attitude and the questionnaire about environmental experiences. Results of the study can be summarized as follow : 1. The variables affected initial status from both models indicated that the environmental experiences were significantly affected the initial status, sex weren t affected the initial status, the environmental attitude from analysis by HLM model was significantly affected the initial status and the environmental attitude from the analysis by LISREL model wasn t affected the initial status. 2. The variables affected rate of change the from both models indicated that the environmental attitude were significantly affected the rate of change, the environmental experiences and sex weren t affected the rate of change. 3. The analysis results from both models indicated that the correlation between the initial status and the rate of change were positive and significantly. 4. The longitudinal analysis of change in environmental knowledge by LISREL model was more explicable the longitudinal analysis of change than HLM model because LISREL model was the lower error